Ozone therapy as an adjuvant for endondontic protocols: microbiological – ex vivo study and citotoxicity analyses (Journal of Applied Oral Science, 2016)
Objectives This study evaluated the antimicrobial efficacy of ozone therapy in teeth contaminated with Pseudomonas aeruginosa, Enterococcus faecalis, and Staphylococcus aureus using a mono-species biofilm model. Parallel to this, the study aimed to evaluate the cytotoxicity of ozone for human gingival fibroblasts. Material and Methods: One hundred and eighty single-root teeth were contaminated with a mono-species biofilm of Enterococcus faecalis, Pseudomonas aeruginosa, and Staphylococcus aureus. Groups were formed: Group I – control; Group II – standard protocol; Group III – standard protocol + ozone gas at 40 µg/mL; and Group IV – standard protocol + aqueous ozone at 8 µg/mL. In parallel, human gingival fibroblasts were submitted to the MTT test. Cells were plated, then ozone was applied as follows: Group I (control) – broth medium; Group II – aqueous ozone at 2 µg/mL; Group III – aqueous ozone at 5 µg/mL; and Group IV – aqueous ozone at 8 µg/mL. Data were submitted to the Kruskal Wallis test and Bonferroni post hoc analyses to assess microbiology and cytotoxicity, respectively (p